2001
DOI: 10.1002/jsfa.985
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and physicochemical changes of barley and pea fibre along the gastrointestinal tract of pigs

Abstract: The degradation of barley and pea ®bres along the gastrointestinal tract (GIT) of pigs and its relation to changes in some of their physicochemical properties were investigated. Ileal and caecal digesta containing pea cotyledon ®bre showed the highest (P < 0.05) swelling (33.1±36.7 ml g À1 DM) and water retention capacity measured by centrifugation (17.9±21.2 g g À1 DM) and by osmotic pressure (9.0±9.1 g g À1 DM). The particle size of barley hull did not change along the GIT (160±207 mm), whereas that of pea c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…However, results obtained in the distal colon were contradictory, because animals fed SBP had a higher WRC and a lower concentration of NSP compared to WB fed animals (293.2, and 313.8 g/ kg DM digesta, respectively, data not shown). Canibe and Bach Knudsen (2001) found no differences in the faecal WRC of pigs fed pea cotyledon (96% digestibility) or pea hull (82% digestibility), even when NSP amount was higher in the faeces of pigs fed pea hull. Thus, it could be suggested that water retention capacity is correlated to the amount of dietary fibre, but also dependent on the composition and structural features of fibre (Bertin et al, 1988).…”
Section: Voluntary Intake and Gastrointestinal Contentsmentioning
confidence: 50%
See 1 more Smart Citation
“…However, results obtained in the distal colon were contradictory, because animals fed SBP had a higher WRC and a lower concentration of NSP compared to WB fed animals (293.2, and 313.8 g/ kg DM digesta, respectively, data not shown). Canibe and Bach Knudsen (2001) found no differences in the faecal WRC of pigs fed pea cotyledon (96% digestibility) or pea hull (82% digestibility), even when NSP amount was higher in the faeces of pigs fed pea hull. Thus, it could be suggested that water retention capacity is correlated to the amount of dietary fibre, but also dependent on the composition and structural features of fibre (Bertin et al, 1988).…”
Section: Voluntary Intake and Gastrointestinal Contentsmentioning
confidence: 50%
“…The content of dietary fibre and the feed particle size influence to some extent the digestive processes in the gastrointestinal tract (GIT, Cummings and Englyst, 1995), the physicochemical characteristics of digesta (Canibe and Bach Knudsen, 2001;Mikkelsen et al, 2004), gut morphology (Jorgensen et al, 1996), and mucosal maturation and integrity (Goodlad et al, 1995;Stark et al, 1995;Brunsgaard, 1998). The effects of dietary fibre and feed form on the gastrointestinal tract physiology can be direct or indirect.…”
Section: Introductionmentioning
confidence: 97%
“…The chemical composition of dry feed and FLF was analyzed by standard methods for determining the content of energy, ash, fat, crude protein, starch, and specific saccharides (2).…”
Section: Dietsmentioning
confidence: 99%
“…The carbohydrate fraction includes the low molecular-weight sugars, starch and various non-starch-polysaccharides (NSP) (Bach Knudsen, 1997). The NSP and lignin are the principal components of cell walls and are commonly referred to as dietary fibre (Theander et al, 1989;Canibe and Bach Knudsen, 2002). Generally, faba beans and peas are rich in starch (422-451 and 478-534 g/kg dry matter, respectively) (DLG, 1999;Jezierny, 2009), whereas lupins have comparatively low levels of starch (42-101 g/kg dry matter) (DLG, 1999;Jezierny, 2010).…”
Section: Nutritional Characteristics Of Soybean Meal Solvent Extract mentioning
confidence: 99%